Principle of proportionality and conditions for participation in a public procurement procedure - Magdalena Taraszkiewicz (Prawo Budżetowe Państwa i Samorządu)
Principle of proportionality is of particular importance when an awarding entity determines conditions for participation in a public procurement procedure. The contracting authority is obliged to determine terms of a contract in a manner adequate to a subject of the contract, in particular with regard to a value, a specificity and a complexity of the contract. The conditions for contractors cannot be excessive, they must be related to the subject of the contract and refer to the minimum requirements that the contractors should meet. Proportionality also means balancing public interest and interests of economic operators. This does not mean, however, that the contracting authority should allow all contractors to participate in the procedure. On basis of the terms of the contract, the contracting authority should define the extend of contractors who guarantee a proper performance of the public contract. Therefore, the contracting authority’s priority is to award a public contract to the contractor who will perform it properly, thus pursuing the public interest.